Water pollution, industrial agglomeration and economic growth: Evidence from China - Huang, Can; Wang, Chien-Ming (Frontiers in Environmental Science, 2022)
This paper investigates the causal relationship between water pollution, industrial agglomeration, and economic growth in 11 Chinese provinces in China. Using a bootstrap autoregressive distributed lag (ARDL) analysis, we examine the estimated models’ stability and investigate the Granger causality relationships between system variables. The results indicate that our estimation provides evidence of a long-run relationship between water pollution, industrial agglomeration, and economic growth in China. The bidirectional running from other water pollution variables is confirmed from the casualty tests in Shanghai and Yunnan. Specifically, the unidirectional causality relationship running from industrial agglomeration and economic growth to water pollution provide statistical evidence of the important role that industrial agglomeration and economic growth play in increasing water pollution.